On optical and physical properties of sea ice in the Baltic Sea - Uusikivi, Jari (Helsingin yliopisto, 2013)
Sea ice has been recognized as one of the key elements of polar and sub-polar seas, including Baltic Sea. The existence of sea ice cover and its properties have influence to many aspects of marine biology, climate and seafaring. This thesis is concentrated on describing physical and optical properties of landfast ice, and also pack ice, in the Baltic Sea. The aim of the thesis is to use measurements to study the interactions between optical and physical properties of sea ice and how these can affect the biology in sea ice. Decade long observations of ice properties were used to construct a statistical model of properties of landfast ice. Temperature was found to be the most important factor determining ice thickness and contribution of snow ice to the ice thickness was determined by the amount of winter time precipitation. Stratigraphy of ice and growth history had influence to the vertical distribution of organisms in the ice cover as snow ice layers and columnar ice layers were found to favor different types of organisms. Thickness of meteoric ice layer, including snow ice and superimposed ice, controlled the albedo of ice cover when no snow cover was on the ice. Based on the observations of fast ice conditions and albedo, the effects of snow thickness and meteoric ice thickness to the albedo of sea ice were formulated as albedo parameterization equations. The optical properties of sea ice with spectral resolution were studied on the landfast sea ice. Emphasis in these studies was given to optical properties in the ultraviolet and visible wavelengths. Organic matter, dissolved and particulate, was the most important factor determining the ultraviolet properties of sea ice cover. The optical properties in the ultraviolet were also actively modified by the living organisms in the ice cover by producing mycosporine like amino acids (MAAs) in relatively high amounts. MAAs are a family of photoprotective compounds that absorb UV radiation efficiently. At the visible part of spectrum the ice by itself and the ...